STUDY KINETIKA PERURAIAN PARTIKEL PADA PEMANFAATAN LIMBAH AMPAS TAHU DAN KOTORAN SAPI SEBAGAI MATERIAL PEMBUATAN BIOGAS - Ni'mah, Lailan (Universitas Lambung Mangkurat, 2014)
The increasing energy demand and the depletion of fossil fuel reserves caused the waterwheel crisis, it is necessary for innovation to generate alternative energy sources. One of the alternative energy is biogas which can be produced from solid waste of tofu production (SWTP). Utilization of solid waste of tofu production (SWTP) to produce biogas can reduce energy consumption from fossil fuels while reducing the accumulation of garbage because so far most of the solid waste of tofu production (SWTP) directly discharged into the environment. Biogas is produced through a process that involves the breakdown of organic material activity of anaerobic microorganisms are bacteria methanogens in a anaerobic reactor (biodigester). Tofu production waste has high acidity so that it needs a buffer in biogas production. One of the buffer which can be utilized is cow manure.The experiment as many as 800 ml of sample was Â entered to the reactor with the capacity of 1 L, then incubated in an anaerobic condition in the room at the temperature of 25-30oC within 30 days. There are 8 variation apply in this research, they are KS:KT=100:0,75:25, 50:50,25:75 and 0:100 at VS of 3%, and KS:AT 50:50 at VS of 2%,4% and 5%. The measured parameter is the biogas volume, methane concentration, carbon dioxide concentration, the ratio of C vs N, total solid (TS) and volatile solid content (VS), volatile fatty acid (VFA),pH and temperature. The gas volume measurement was done every day using gasholder while methane concentration was measured by gas chromatography (GC).The experiment result shows that the composition of cow manure and SWTP at VS of 3% KS:AT = 50:50 shows the highest methane concentration compared to the other compositions. The mathematic model as first order of reaction rate equation can approach the experiment result.Â Keywords:solid waste of tofu production, cow manure, biogas, and biogas's production model.